THE GREAT MOSQUE OF SURAKARTA STRUCTURE DESIGN - Firdaus, Al-farisi
Indonesia, a predominantly Muslim country, has the need of mosque as a place of worship. Today, there are various mosque architectural design to support comfort in worship. It is a challenge for civil engineer to build a strong, secure, and comfortable mosque structures. The Great Mosque of Surakarta is intended to be built for its purpose. The structure itself consist of 8 levels (5 stories + 3 basement levels) with a distant gap between columns. The material component is reinforced concrete for the main structure and structural steel on the roof frame structure. The designer structured is classified as seismic design category D which is designed with special moment frame method. The purpose of this assignment are to create structural model based on the reference architectural plan, analyze the structural behaviour, provide dimension of concrete structure with the detail of reinforcement for each component of the main structure, and checks the capacity of steel structur element with the detail of steel joints for roof frame structure. On the planning, structure is designed for earthquake resistant building. At the end of the design process, the writer can conclude that The Great Mosque of Surakarta has met the design criteria and ready to build based on the spesification and methods used.